Silicate refractory brick waste as quartz sand filler replacement in MOC-based composites - Anna-Marie Lauermannová; Michal Lojka; Oskar Chmel; Ondřej Jankovský; Martina Záleská; Adam Pivák; Milena Pavlíková; Zbyšek Pavlík (Case Studies in Construction Materials)
This study focuses on the design and development of environmentally sustainable construction composites with an accent on the utilization of secondary raw material sources or wastes, whose secondary purpose was not discovered yet and are landfilled or downcycled only. This approach leads to a significant reduction in the environmental burden resulting from activities related to the construction industry and thus ensures its sustainability. Spent refractories are a potential candidate for this purpose. The presented experiment deals with the replacement of standard quartz sand filler by silicate refractory brick waste (SW) in magnesium oxychloride- (MOC-) based composite materials. The standard filler was replaced either partially, fully, or in excess in order to fully uncover the potential of SW as a filler in construction composites. As a matrix, MOC phase 5 (Mg3(OH)5Cl∙4 H2O), which is considered an eco-friendly alternative to Portland cement, was used, as it is known to be able to contain large amounts of filler of various origins. This way, three types of construction utilizing a waste material, which would otherwise end up landfilled, were prepared. To assess the effect of the filler replacement, a reference MOC-based composite using quartz sand as the only filler was prepared. In the SW-filled composites, the replacement ratio was 50, 100, and 150 % by weight. The introduction of SW caused an increase in compressive strength for all of the prepared samples, most significantly for composite SW50, in which the quartz sand was replaced by 50 wt%. The compressive strength of this composite reached a mean value of 101.30 MPa, which is 25 % higher than the reference composite. This value exceeds the lower compressive strength limit for a construction composite to work as a high-performance concrete by more than 20 MPa. Furthermore, all of the prepared composites show very high flexural strength values (over 30 MPa). The microstructural analysis also proved that the presence of capillary pores with a diameter range between 100 and 1000 nm, which are generally responsible for the water-induced damage in MOC-based composites was significantly decreased with the replacement of quartz sand by SW in the amount of 50 wt%.